Metamemória e Envelhecimento - Grace Ane Morgana Cavalcante de Queiroz (2022)
During aging, cognitive abilities change and the inability to effectively monitor, these changes can have negative consequences. Within this context, the subjective memory complaints may indicate the existence of a possible decline in cognitive functioning. In order to investigate the accuracy of metacognitive monitoring during the aging process, we evaluated the performance of young adults, middle-aged adults and older adults in episodic memory tasks. We also investigated the relationship between subjective memory complaints and objective performance in older adults. All participants performed an experimental task, in which they were instructed to study neutral images presented in different quadrants of the computer screen. They should also provide a judgment of learning for each image, on a scale that varied between 1 and 10. The test phase consisted of a recognition task, confidence judgment for the response and a source monitoring task. The results revealed a lower performance of older adults to correctly recognize the images studied, as well as higher confidence estimates for errors and false alarms, compared to younger adults. The accuracy of judgments of learning did not differ between groups, however, it only predicted performance on the recognition task. The results of study two did not reveal a significant difference between the older adult’s performance with and without memory complaints in the objective tasks, nor in the accuracy of the metacognitive monitoring. However, the group with subjective memory complaints had higher anxiety scores than those with no complaints. We conclude that like the episodic memory, metacognitive monitoring is influenced by age and impairments can already be observed in intermediate age groups. We also concluded that the memory complaints reported by the participants of this study do not correlate with objective performance and with metacognitive monitoring, being better explained by the scores on the anxiety scale.